MOLECULAR-GENETIC CHARACTERISTICS OF PRIMARY TUMOR AND METASTATIC LYMPHATIC NODES IN BREAST CANCER - V. K. Bozhenko; I. D. Trotsenko; E. A. Kudinova; S. G. Vardanyan; M. V. Zakharenko; V. A. Solodkiy; M. V. Makarova (Сибирский научный медицинский журнал, 2019)
The purpose of systemic treatment in patients with breast cancer is based largely on the molecular characteristics of the primary tumor, but many clinical recommendations suggest also the study of metastatic nodes with an assessment of their receptor status (estrogen receptor ER, progesterone receptor RP, human epidermal growth factor receptor 2 Her2/neu). This is due to the fact that according to numerous studies, the discrepancy between the status of the primary tumor and the secondary nodes can reach high rates: 3–54 % for ER, 5–78 % for RP, and 0–34 % for Her2/neu. At the same time, more and more data actively demonstrate the imperfection of immunohistochemical analysis and the need to study additional parameters to improve the quality of diagnosis of patients with breast cancer. Material and methods. A morphological and immunohistochemical study of the tumor tissue of the primary node and axillary lymph nodes was performed in 199 patients with breast cancer (T1-3N0-3M0) using standard methods, and RT-PCR was also studied with the expression of 24 genes. Results. The incidence of differences between the molecular phenotypes of the main tumor and metastatic axillary lymph nodes was 26 (26 %) of 99 cases. Most often, differences were noted in cases of breast cancer with luminal A type – 13 cases (50 %). According to the results of a comparative PCR analysis of tissue samples from the primary tumor and metastatic regional lymph nodes, only the expression of the CD68, ERSR1, GRB7 and MMD11 receptors was statistically significant. Conclusion. The results indicate the need for an integrated approach and additional methods for the diagnosis of breast cancer, which will undoubtedly improve the quality of planning and the effectiveness of systemic treatment in patients with breast cancer.